A comparative study of complications of vivax and falciparum malaria in Dehradun, India - Singh, S. P.; Singh, Ragini; Ahmad, Niaz (International Journal of Research in Medical Sciences, 2017)
Background: Traditionally Plasmodium falciparum has been considered to cause severe malaria while Plasmodium vivax is known to cause benign malaria. However many recent studies have shown that Plasmodium vivax is also responsible for many cases of severe malaria. There is scarcity of data on this topic from this region. The present study was conducted to find out clinical and pathological manifestations of vivax and falciparum malaria in Dehradun. Methods: The study period was of one and half years, from January 2012 to June 2013. Patients of 18 years of age or above it who were smear positive or antigen positive were included in the study. Results: one hundredand thirty nine patients were found to be suffering from malaria. 90 (64.7%) had vivax malaria, while 49 (35.3%) patients suffered from falciparum. The study of morbidity profile showed that the complications related to severity, earlier attributed to only falciparum is equally seen in vivax case. Low platelet count was the commonest finding in both groups. Other complications seen in both groups were those of severe anemia, cerebral malaria, ARDS, renal failure, hepatitis, leucocytopenia, pancytopenia, and shock. Mortality in the two groups was of the same order. Conclusions: Vivax malaria causes significant mortality and morbidity. The morbidity and patterns are almost similar in both vivax and falciparum malaria.